Pigmented villonodular synovitis occurring in the temporomandibular joint. Issue 4 (August 2019) - Nomura, Fuminori; Ariizumi, Yosuke; Kiyokawa, Yusuke; Tasaki, Akihisa; Tateishi, Yumiko; Koide, Nobuaki; Kawabe, Hiroaki; Sugawara, Takashi; Tanaka, Kentaro; Asakage, Takahiro
Abstract: Objective: Pigmented villonodular synovitis occurring in the region of the temporomandibular joint is a rare disease, requiring a review of the treatment method, follow-up period. Method: Refer to the past literature, along with a retrospective search. Results: An excision, including the skull base bone, was performed in all cases; however, recurrence was found in one case on which fractional excision was performed. Past reports have also indicated that en bloc resection was considered desirable. Conclusion: It is necessary to perform en bloc resection on patients with pigmented villonodular synovitis occurring in the region of the temporomandibular joint. Furthermore, due to reported cases of recurrence after a long period of time, follow-up observations of about 10 years are considered necessary.